Health-related quality of life of individuals with multiple sclerosis from the Magallanes Region of Chile - Retamal-Matus, Héctor; Fernández-Calderón, Ramiro; Fernández-Elgueta, Alejandra; Martínez-Alarcón, Carolina; Montaña-Yañez, Gastón (Revista Chilena de Salud Pública, 2020)
Introduction: Multiple sclerosis (MS) is an autoimmune, chronic, inflammatory and demyelinating disease that affects the central neuro system (CNS) and patients’ quality of life. This is particularly relevant as MS impacts young individuals, during their productive years. Aim: To describe the demographic characteristics and health-related quality of life of individuals with MS in the Magallanes and Chilean Antarctic Region. Materials and methods: A descriptive study of individuals with MS was conducted; demographic information was collected, and health-related quality of life was assessed with the SF-36 v.2 instrument. Results: A total of 40 patients, between 21 to 65 years of age (57.5% women) were evaluated. They had MS for an average of 7.59 ± 7.38 years. In the SF-36 v.2, the lowest average scores were in the dimensions of Vitality (53.75 points) and General Health (61.00 points), while the highest scores were in Social Functioning (72.50 points) and Physical Functioning (71.63 points). There was no sex-based difference in quality of life. Conclusions: MS produces a gradual and varied decline of neurological functions, leading to a reduction of quality of life, mainly in the dimensions of Vitality and General Health perception